A general metal-free route towards the synthesis of 1, 2, 3-triazoles from readily available primary amines and ketones. Issue 14 (8th January 2016) - Thomas, Joice; Jana, Sampad; John, Jubi; Liekens, Sandra; Dehaen, Wim
Abstract : A metal-free route towards different 1, 2, 3-triazole heterocycles was accomplished by using inexpensive and readily available ketones and primary amines. This reaction is very general and was extended to functionalize different amino esters, dendrimers and natural products. Abstract : An unprecedented approach that enables the direct and selective preparation of 1, 5-disubstituted 1, 2, 3-triazoles from abundantly available building blocks such as primary amines, enolizable ketones and 4-nitrophenyl azide as a renewable source of dinitrogen via an organocascade process has been developed. Furthermore, this efficient methodology also enables the synthesis of fully functionalized and fused N-substituted heterocycles.